Penerapan Complex Proportional Assessment (COPRAS) Dalam Penentuan Kepolisian Sektor Terbaik - Ginting, Garuda; Alvita, Suha; Mesran, M; Karim, Abdul; Syahrizal, Muhammad; Daulay, Nelly Khairani (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
In determining the best Sector Police, many criteria must be had by every Sector Police to be the best. Some of the criteria used to determine the best Sector Police are Polsek services, completion of the crime, number of personnel, cleanliness of the Sectoral Police, and number of criminal acts. Determination of the best Sector Police to improve the performance of personnel so that they are encouraged to be better at doing their jobs than before. To avoid mistakes and be precise in determining the best Police Sector, a decision support system is needed. In this study, a case will be raised, namely finding the best alternative based on the existing criteria using the Complex Proportional Assessment (COPRAS) method. The COPRAS method is used to analyze different alternatives and estimate alternatives according to the level of utility where the values of the attributes are expressed in intervals to increase efficiency and increase accuracy in the decision-making process.